DNA Profile of Pacific White Shrimp, L. vannamei Infected by Taura Syndrome Virus Using Single Strand Conformation Polymorphism (SSCP) Analysis - Permana, Gusti Ngurah; Moria, Sari Budi; haryanti, haryanti (Indonesian Aquaculture Society (MAI), 2016)
The shrimp infected by Taura syndrome virus (TSV) can survive until harvesting time. At this phase, the growth of this shrimp is relatively normal but it is referred as TSV carrier. This research is expected to provide a recommendation in effort to prevent the occurrence of TSV infection. Therefore, this study was aimed to evaluate the DNA polymorhism of Pacific white shrimp L. vannamei infected by TSV. A total of 60 samples of L. vannamei were collected from SPF (specific pathogen free)-Florida, F1-healthy, F1-tolerance (it is can life normally after infected by TSV), and F1-moribund (diying after infected by TSV). The samples were analysis using PCR with IQ-2000 KIT to determine the positive infection of samples. DNA profile of white shrimp, L. vannamei was significantly different from SPF Florida, F1-moribund, and F1-healthy shrimp. This expression may control the defense mechanism. This can be ascribed to the reason that shrimp survived from TSV infection had a higher amount of locus (3 loci) that were detected from DNA polymorphism of gene in white shrimp contributed to a gene control that was determined from allele variation. Two important alleles (200 bp and 220 bp) unique may be associated with tolerant trait. Those loci only found in F1-tolerance shrimp. However to prove that further necessary to sequences a nucleotide of three loci as responsible for resistance to TSV infection.